Impact of Climate Change and Its Variability on the Rainfall Pattern in Sarawak River Basin - Charles, Hin Joo Bong; Ting, Sie Yew; Rosmina, Ahmad Bustami; Putuhena, F.J. (2009)
Climate change due to global warming is expected to play a role in determining the availability of water in years to come. An understanding on the potential effects of climate change on the hydrology of a river basin is important in preparing adaptability measures that will produce benefits even if climate does not change. For the case of Sarawak River Basin, long term impacts of climate change on the local scale is still not clear. Thus, a detailed study is needed and this paper aims at presenting the findings of a preliminary study on the rainfall pattern for Sarawak River Basin done by the authors of this paper. The trends for temperature and evaporation rate for a station in the basin are also presented. Some adaptability measures in preparing for the potential effects of climate change for the basin will also be discussed.